Characteristics of goods vehicles in Singapore - Goh, Teck Jin. (2008)
The objective of this dissertation is to identify the characteristics of goods vehicles in the freight transport industry in Singapore. Identifying the characteristics of good vehicles and their associated trends is important in the context of urban planning.